2020
DOI: 10.1016/j.ajpath.2019.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of the Endothelial Secretome Identifies RC0497 as Diagnostic of Acute Rickettsial Spotted Fever Infections

Abstract: Mediterranean spotted fever is a reemerging acute tick-borne infection produced by the a-proteobacterium, Rickettsia conorii. Rickettsia conorii infects vascular endothelial cells producing disseminated plasma leakage, manifesting as nonspecific fever, headache, and maculopapular rash. Because there are no available tests of early infection, Mediterranean spotted fever is often undiagnosed and untreated, resulting in significant mortality. To address this critical need, we have applied a quantitative proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Recently, we have characterized RC0497 as an ampD domain containing N-acteylmuramoyl-L-alanine amidase involved in peptidoglycan hydrolysis and demonstrated its localization on the septal regions in dividing bacteria and on the membranes of vesicles protruding from the rickettsial cell wall [28]. A simultaneous study has further revealed that RC0497 is also secreted into the culture supernatants during infection of endothelial cells in vitro and is readily detectable in the serum of infected patients, projecting it as a promising candidate for the design and development of rapid diagnostics [29]. Additionally, heat shock chaperone (groEL), cold shock protein of CSP family (cspA), CarD like transcriptional regulator, and anti-toxins (vapB and anti-toxin of relE) were ubiquitously expressed in both infected HMECs and tick cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have characterized RC0497 as an ampD domain containing N-acteylmuramoyl-L-alanine amidase involved in peptidoglycan hydrolysis and demonstrated its localization on the septal regions in dividing bacteria and on the membranes of vesicles protruding from the rickettsial cell wall [28]. A simultaneous study has further revealed that RC0497 is also secreted into the culture supernatants during infection of endothelial cells in vitro and is readily detectable in the serum of infected patients, projecting it as a promising candidate for the design and development of rapid diagnostics [29]. Additionally, heat shock chaperone (groEL), cold shock protein of CSP family (cspA), CarD like transcriptional regulator, and anti-toxins (vapB and anti-toxin of relE) were ubiquitously expressed in both infected HMECs and tick cells.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was carried out with Fiji 1.53c (ImageJ, NIH, Bethesda, MA, USA), where we evaluated the positive or double-positive cells or respective nuclei in the tumor area and normalized the results as positives per standard field of view. Image correlation of the DAPI and LPPR5 signal was performed with an automated CellProfiler 2.2 pipeline (Broad Institute, Boston, FL, USA) [ 54 , 55 ]. In this setting, correlation is defined as the correlation between a pair of images I and J, calculated as Pearson’s correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the use of biotechnological advances such as quantitative proteomic analysis of the endothelial secretome ( 74 ) and single cell RNA-sequencing of infected blood vessels will elucidate differential proteins/targets in ECs subject to bacterial and viral infection.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%